Imaging spectrum of primary malignant renal neoplasms in children - Rama Anand; Mahender K Narula; Isha Gupta; Vikas Chaudhary; Subhasis Roy Choudhury; Manjula Jain (Indian Journal of Medical and Paediatric Oncology)
Wilms′ tumor (WT) is the most common abdominal tumor in children. Many pediatric renal tumors in the past were categorized as WT; however, in recent years, several specific renal tumors have been recognized as distinct pathological entities. The age and clinical presentation of the child and distinctive imaging features may help in reaching a specific diagnosis in most cases. This is important as it has implications on the pre-operative diagnostic work-up and prognosis of the child. However, it is often not possible to differentiate one from the other pediatric renal tumor on the basis of imaging alone, and the final diagnosis is often made at histological examination of the surgical specimen. This article reviews the imaging features of primary malignant renal neoplasms in children along with their clinical presentation and pathological features.